(untitled) (GUB Journal of Science and Engineering, 2022)
Garments washing is the process of altering the aesthetic look, luxury, fashion, and comfortability of a garment after it has been manufactured. Most garments nowadays go through many washing processes before being sold in retail outlets. As denim is one of the most adaptable fabrics available today, the aesthetics may be reinvented in an infinite number of ways through garments washing techniques. Because of the rough and stiff nature of jute fiber, it is not currently used as a popular material for garments manufacturing. A sustainable option may be possible by using jute and cotton blended fabric in manufacturing. Moreover, enzyme is a naturally occurring product. Therefore, the product is environmentally friendly. In a washing bath, the enzyme functions as a catalyst to hydrolyze fiber, soften the fiber surface, and decrease pilling. The experiment was conducted on a 70 percent cotton, 30 percent jute blended fabric with a weave construction of 2/1 twill. The goal of this study is to observe how an industrial enzyme wash affects a jutecotton blended denim fabric. For this investigation, neutral enzyme was used. Finally, the raw and washed samples was compared in terms of physical parameters such as EPI, PPI, GSM, warp strength, and weft strength. This research may unlock a way for enzymatic treatment on jute cotton blended denim fabric. GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 8, Dec 2021 P 24-28